HEDONIC VALUE DAN UTILITARIAN VALUE SEBAGAI PREDIKTOR TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI MEDIATOR - Tommy Ruslim (MANAJEMEN DEWANTARA, 2023)
The travelling necessity becomes the most wanted thing for many people at present days, either for business purpose, vacation purpose, or others. This study aimed to predict the customer loyalty toward “T” Online Travel Agent (OTA) by using 150 respondents as samples. The result of this study concludes that utilitarian value becomes a positive and significant predictor of customer satisfaction, but on the other hand, it does not serve as a significant predictor of customer loyalty. Meanwhile, utilitarian value becomes a positive and significant predictor of customer loyalty through customer satisfaction (full mediation). In addition, hedonic value serves as a positive and significant predictor of customer satisfaction and loyalty, as well as a positive and significant predictor of customer loyalty through satisfaction (partial mediation).